A kind of aluminum alloy containing scandium and preparation method thereof

By doping scandium and other metal elements into aluminum, and using optimized doping method and rapid cooling treatment, the segregation and high cost problems in the preparation of aluminum scandium alloys are solved, the strength and elongation of the alloy are improved, and an environmentally friendly and efficient preparation process is achieved.

CN118910442BActive Publication Date: 2025-04-29DAYUAN HI-TECH (JIANGSU) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410951705.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-15
Publication Date
2025-04-29
Estimated Expiration
2044-07-15

AI Technical Summary

Technical Problem

The existing aluminum scandium alloy preparation methods have problems such as high process requirements, low current efficiency, high energy consumption, high cost and unenvironmental protection. The aluminum scandium alloy produced by the doping method has coarse grains and serious composition segregation, resulting in insufficient strength, low fracture toughness and post-break elongation.

Method used

By doping scandium and zinc, copper, magnesium and zirconium into the aluminum, the optimized doping method is used, and the aluminum content in the primary alloy of aluminum and other metals is defined, combining rapid cooling and interface processing, reducing segregation and refining grains.

Benefits of technology

It improves the strength and elongation of aluminum scandium alloy, reduces segregation phenomenon, improves the performance of the alloy, reduces manufacturing costs, and improves environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118910442B_ABST
    Figure CN118910442B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of aluminum alloy manufacturing, and specifically relates to a scandium-containing aluminum alloy and a preparation method thereof, wherein the scandium-containing aluminum alloy includes the following weight fraction components: 7-9% Zn, 1.6-2% Cu, 1.8-2.2% Mg, 0.1-0.2% Zr, 0.02-0.05% Sc, and the balance is Al. In the preparation method, an optimized and innovative blending method is adopted to limit the aluminum content in the primary alloy of aluminum and other metals, thereby reducing the occurrence of segregation in alloy production. At the same time, a rapid cooling step and an alternating current + direct current overlapping method are used to oxidize the surface of the prepared aluminum alloy during the cooling and temperature reduction stage and the interface treatment process, further reducing the problems of uneven element distribution and limited oxide film thickness in alloy production, comprehensively improving the mechanical properties and wear resistance and corrosion resistance of the synthetic material, and having very strong practical application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aluminum alloy manufacturing, and specifically relates to a scandium-containing aluminum alloy and a preparation method thereof. Background Art

[0002] Scandium metal has the functions of refining grains, inhibiting alloy recrystallization, and improving corrosion resistance in aluminum alloys, which can significantly improve the strength, plasticity, high temperature performance, corrosion resistance and welding performance of the alloy. Therefore, aluminum-scandium alloy is considered to be a new generation of high-performance aluminum alloy structural materials for aerospace, ships, and weapons. In addition, studies have found that the aluminum-scandium film deposited from the aluminum-scandium alloy target can not only maintain the same electrical conductivity as high-purity aluminum, but also improve corrosion resistance, especially significantly inhibiting electromigration and stress migration. Therefore, aluminum-scandium alloy palladium is also considered to be a new generation of wiring materials for large-scale integrated circuits. In summary, aluminum-scandium alloy has broad application prospects in high-tech fields such as aerospace, electronic information technology, etc. due to its excellent performance. With the rapid development of science and technology, the demand for high-performance and high-quality aluminum-scandium alloys is also increasing.

[0003] The existing preparation methods of aluminum-scandium alloys mainly include molten salt electrolysis, aluminothermic reduction, powder metallurgy and blending.

[0004] The lava electrolysis method mainly involves argon protection in a Na3AlF6-KCl-NaCl-ScF3 or ScCl3-KCl-NaCl or Na3AlF6-LiF-Sc203 system, at a temperature of 850°C to 1100°C, and molten salt electrolysis with a graphite cathode to prepare an aluminum-scandium alloy. The prior art discloses a molten salt electrolysis method for an aluminum-scandium master alloy, in which a fluoride molten salt M3AlF6-AlF3 is used as the basic electrolyte system in a prebaked anode molten salt electrolytic cell with point-type feeding, and aluminum oxide and a scandium-containing compound are used as raw materials. The metal aluminum and metal scandium are electrolytically precipitated in different cathode areas in the same electrolytic cell by independent feeding, and alloyed, thereby obtaining an aluminum-scandium master alloy with a scandium content of 1.5% to 3.0% and a total content of aluminum and scandium greater than 99%. However, this method has high process requirements, low current efficiency (65% to 80%), severe corrosiveness of fluoride salts, easy corrosion and failure of electrolytic cells and electrode materials, large energy consumption, high cost, and is not environmentally friendly.

[0005] The powder metallurgy method is to fully mix a certain proportion of high-purity metal scandium powder and aluminum powder, evenly press them into shape, and then perform heat treatment processes such as sintering under argon protection to obtain an aluminum-scandium intermediate alloy. A prior art announcement discloses a method for preparing an aluminum-scandium alloy target blank, which uses a powder sintering method to prepare an aluminum-scandium alloy target blank containing 0.1% to 15% scandium. Another prior art discloses an aluminum-scandium alloy target blank and a preparation method thereof, which uses a powder sintering method to prepare an aluminum-scandium alloy palladium blank containing 16% to 50% scandium. In addition, there is also a prior art disclosure of a high-scandium-content aluminum-scandium alloy and a preparation method thereof, which uses a powder sintering method to prepare an aluminum-scandium alloy containing 55% to 70% scandium. However, the above methods all require expensive metal powders as raw materials, which are relatively costly, and metal scandium powders and aluminum powders are easily oxidized and have a high oxygen content, which affects the purity of the product, and the alloy density is difficult to reach the alloy density prepared by smelting. The aluminothermic reduction method for preparing aluminum-scandium alloy mainly includes the scandium fluoride vacuum aluminothermic reduction method and the scandium fluoride direct aluminothermic reduction method. The prior art discloses a method for preparing aluminum-scandium alloy by aluminothermic reduction of scandium fluoride. The method is to load the raw materials scandium fluoride and aluminum into a graphite crucible, and then place it in a vacuum reactor, evacuate the low-temperature degassing and evacuate the vacuum to -0.1MPa, heat up and melt the aluminum and raise the temperature to 1100℃~1350℃, stir continuously, control the temperature until the surface of the melt is clear, cool down and cast, and obtain the aluminum-scandium alloy. However, the higher the scandium content of the aluminum-scandium alloy obtained by this method, the more serious the component segregation, and the fluorine element will also be introduced. Another prior art discloses a method for preparing aluminum-scandium alloy by aluminothermic reduction, which uses powdered scandium oxide as raw material, NH4HF2, NaF and alkali metal chloride as fluorinating agent, flux and flux, and aluminum as reducing agent, and heats to 850°C to 1100°C in an alumina or graphite crucible, and keeps the temperature for a period of time to cast into an alloy ingot. The mass content of scandium in the alloy ingot is 1% to 3%, the sum of the mass content of scandium and aluminum is greater than 99%, and the yield of scandium is greater than 80%. Therefore, this method can only prepare aluminum-scandium alloys with low scandium content, and impurities are introduced during the preparation process, which has great limitations.

[0006] Compared with other methods, the cross-blending method is simple and low-cost, and is currently the most widely used method in industrial manufacturing. Specifically, the metal scandium and metal aluminum are pre-mixed and then mixed into the aluminum liquid in the presence of a protective gas to be melted, kept warm for a sufficient time, and injected into the mold after being fully stirred to obtain an aluminum-scandium intermediate alloy. However, the aluminum-scandium compound formed by this method has coarse grains and very serious component segregation, resulting in the aluminum-scandium alloy finally prepared having problems such as insufficient strength, low fracture toughness and elongation after fracture, which seriously limits the further development and application of the cross-blending method. Therefore, it is particularly important to develop a method for producing and preparing aluminum alloys containing scandium using the cross-blending method to solve the problems of coarse grains and serious component segregation of aluminum-scandium alloys produced by the cross-blending method. Summary of the invention

[0007] In view of the problems existing in the current preparation method of scandium-containing aluminum alloys mentioned above, the present invention provides a scandium-containing aluminum alloy and a preparation method thereof, by doping scandium and zinc, copper, magnesium, and zirconium into aluminum, using a doping method and optimizing and innovating the original doping method, limiting the content of aluminum metal in the primary alloy of aluminum and other metals, as well as rapid cooling and interface treatment, reducing the occurrence of segregation in alloy production, refining alloy grains, and improving the strength and ductility of the aluminum-scandium alloy. The specific technical scheme is as follows:

[0008] First, the present invention provides a method for preparing a scandium-containing aluminum alloy, comprising the following steps:

[0009] S1 Ingot production: Metal aluminum is placed in a heating furnace with protective gas to melt, stir and mix, and then cooled to form aluminum-zinc alloy ingots, aluminum-copper alloy ingots, aluminum-magnesium alloy ingots, aluminum-zirconium alloy ingots and aluminum-scandium alloy ingots;

[0010] S2 Melting casting: The ingot and metal aluminum prepared in S1 are placed in a heating furnace with a protective gas to be heated into a molten liquid, and then the molten liquid is poured into a casting mold and pressure-cast to form a casting;

[0011] S3 surface treatment: wash the castings made in S2 and apply rust inhibitor;

[0012] S4 heat treatment: the casting after surface treatment is put into a heating container for reheating;

[0013] S5 rapid cooling: rapidly cooling the heat-treated casting to room temperature;

[0014] S6 secondary heat treatment: the cooled casting is put into a heating container for reheating;

[0015] S7 interface treatment: Use low voltage DC and AC superimposed current to treat the casting with a bipolar oxide film.

[0016] Furthermore, in the steps S1 and S2, the temperature of the heating furnace is 730-750° C., the stirring time is ≥1 hour, the protective gas is nitrogen or argon, and the pressure of the heating furnace is 10-15 mmHg.

[0017] Furthermore, in the step S1, the aluminum content in the aluminum-zinc alloy ingot, the aluminum-copper alloy ingot, the aluminum-magnesium alloy ingot, the aluminum-zirconium alloy ingot and the aluminum-scandium alloy ingot is 80% to 90%.

[0018] Furthermore, in step S2, protective gas is sprayed during pressure casting, the protective gas temperature is 450-550° C., and the spraying pressure is 2-4 bar.

[0019] Furthermore, in step S3, the washing solution is a 10% nitric acid solution, and the rust inhibitor is a tribasic hydroxy acid.

[0020] Furthermore, in step S4, the heating temperature is 400-500° C., and the heating time is 100-150 min.

[0021] Furthermore, in step S5, the rapid cooling time is ≤2s; and the cooling medium is liquefied nitrogen or water.

[0022] Furthermore, in step S6, the heating temperature is 115-125° C., and the heating time is 12-24 hours.

[0023] Furthermore, in step S7, the bipolar oxide film treatment voltage is ≤20V, the DC / AC overlapping current is 40% AC and 60% DC; and the oxide film thickness is ≥100 μm.

[0024] The invention also discloses a scandium-containing aluminum alloy, which is composed of the following weight parts: 7-9% Zn, 1.6-2% Cu, 1.8-2.2% Mg, 0.1-0.2% Zr, 0.02-0.05% Sc, and the balance is Al.

[0025] Compared with the prior art, the scandium-containing aluminum alloy of the present invention has the following beneficial effects:

[0026] 1) The scandium-containing aluminum alloy prepared in the present invention is prepared by doping scandium and zinc, copper, magnesium and zirconium elements into aluminum, using a doping method and optimizing and innovating the original doping method, limiting the aluminum content in the primary alloy of aluminum and other metals, as well as rapid cooling and interface treatment, thereby reducing the occurrence of segregation in alloy production, refining the alloy grains, and improving the strength and ductility of the aluminum-scandium alloy.

[0027] 2) In view of the phenomenon that component segregation is easy to occur in the production by the doping method, the present invention limits the content of zinc, copper, magnesium, zirconium and scandium doped in the intermediate alloy to 10% to 20% during the ingot production process. In this way, the segregation phenomenon caused by too little content of the doped alloy can be suppressed in the melt, thereby reducing the uneven distribution of the doped alloy in the aluminum liquid, thereby improving the alloy performance.

[0028] 3) The inventors have found in long-term research that scandium and magnesium are prone to rapid grain movement during the cooling process, resulting in obvious segregation. In view of the above phenomenon, the inventors creatively use a rapid cooling operation in the aluminum-scandium alloy, which can reduce the movement speed of the grains. In this way, magnesium and scandium elements will not only not segregate, but will be distributed more evenly, which can greatly reduce the low-temperature brittle failure and microcracks that occur when impurities segregate to the grains, and improve the toughness and tensile strength of the alloy material.

[0029] 4) The surface of aluminum alloy is usually covered with a layer of oxide film, but this oxide film is very thin and cannot effectively protect the aluminum alloy. Therefore, electrochemical methods are usually used to increase the thickness of the aluminum alloy oxide film. However, in actual work, the native oxide film on the surface of the aluminum alloy will hinder the current. When the thickness of the oxide film becomes thicker and thicker, the voltage needs to be increased, resulting in a significant increase in power consumption. In addition, high heat will be generated due to long-term operation at high voltage, and the film layer will burn, making it impossible to further thicken the film layer. In response to the above problems, the inventors used an overlapping method of alternating current + direct current to oxidize the surface of the prepared aluminum alloy. By controlling the generation speed and adjusting the size and number of pores on the surface of the aluminum alloy, the thickness of the oxide film can be increased to more than 100μm, greatly improving the wear resistance, corrosion resistance and surface strength of the aluminum alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 is a SEM image of the aluminum alloy in Example 1 of the present invention;

[0031] Figure 2 is a TEM image of the aluminum alloy in Example 1 of the present invention;

[0032] Figure 3 This is the XPS graph of the aluminum alloy in Example 1 of the present invention;

[0033] Figure 4 This is the XRD diagram of the aluminum alloy in Example 1 of the present invention. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solution and advantages of the present invention more clear, the technical solution of the present invention will be clearly and completely described below in conjunction with embodiments.

[0035] Example 1

[0036] The present embodiment provides a scandium-containing aluminum alloy, which is specifically composed of the following parts by weight: 0.02% Sc, 2% Mg, 1.8% Cu, 8% Zn, 0.15% Zr, and the balance is Al.

[0037] This embodiment also provides a method for preparing a scandium-containing aluminum alloy, which specifically comprises the following steps:

[0038] S1 Ingot production: Metal aluminum is placed in a heating furnace with protective gas to melt, stir and mix, and then cooled to form aluminum-zinc alloy ingots, aluminum-copper alloy ingots, aluminum-magnesium alloy ingots, aluminum-zirconium alloy ingots and aluminum-scandium alloy ingots;

[0039] Specifically, according to the composition of a scandium-containing aluminum alloy provided in this embodiment, the corresponding mass parts of metal aluminum and metal zinc, copper, magnesium, zirconium and scandium are weighed, and the metal aluminum is respectively put into a vacuum induction furnace or a reverberatory furnace for heating and smelting with metal zinc, copper, magnesium, zirconium and scandium, and the purity of the above metals must reach 99.99% or above. During the smelting process, nitrogen or argon needs to be added to the vacuum induction furnace or the reverberatory furnace as a protective gas and kept sealed. The pressure in the vacuum induction furnace or the reverberatory furnace is 15 mmHg. The smelting temperature is 730°C, and the stirring and heating time is 2 hours. After the heating and stirring are completed, the prepared alloy is naturally cooled into an ingot, including an aluminum-zinc alloy ingot, an aluminum-copper alloy ingot, an aluminum-magnesium alloy ingot, an aluminum-zirconium alloy ingot and an aluminum-scandium alloy ingot. The aluminum alloy content in the above-mentioned ingot is 82%, so that in the subsequent casting process, the segregation phenomenon caused by the addition of alloying elements such as zinc, copper, magnesium, zirconium and scandium that do not meet the standards can be suppressed, and the uneven distribution of alloying elements can be avoided. At the same time, the loss of expensive alloying elements can be minimized.

[0040] S2 Melting Casting: The ingot and metal aluminum obtained in S1 are placed in a heating furnace with a protective gas to be heated into a molten liquid, and then the molten liquid is poured into a casting mold and pressure-cast to form a casting;

[0041] Specifically, the ingot and metal aluminum prepared in S1 are added into a vacuum induction furnace or a reverberatory furnace according to the designed metal content. The reaction conditions are the same as S1. It should be noted that the optimal heating time in this step is 2 hours. After all the metals are smelted and mixed evenly, the dissolved molten metal is poured into the mold and gravity-casted into a casting to ensure that the molten metal can penetrate into every corner of the mold to avoid gaps in the casting. Protective gas protection is still required during the pouring of the molten metal and pressure casting to minimize the contact between the molten metal and the air and prevent oxidation of the metal aluminum. The protective gas here needs to be heated to 500°C in advance and sprinkled on the surface of the molten metal with a spray gun. The spraying pressure needs to be maintained at 3 bar.

[0042] S3 surface treatment: wash the castings made in S2 and apply rust inhibitor;

[0043] Specifically, the surface of the cooled casting is washed with nitric acid to remove the oxide film formed on the surface. After washing, a rust inhibitor is applied to the surface of the casting to form an oil protective film on the surface of the casting to cut off air and prevent oxidation.

[0044] S4 heat treatment: the casting after surface treatment is put into a heating container for reheating;

[0045] Specifically, the casting that has undergone S3 surface treatment is placed in a vacuum induction furnace or a reverberatory furnace and heated to 450° C. This step can heat the alloy elements that have been segregated in the previous step, causing them to diffuse and move inside the grains to achieve homogenization.

[0046] S5 rapid cooling: rapidly cooling the heat-treated casting to room temperature;

[0047] Specifically, liquid nitrogen or cooling water is used to quickly cool the heat-treated casting to room temperature, and the cooling time is less than 2 seconds. Rapid cooling is used in this embodiment, which can suppress the segregation phenomenon caused by the fast movement speed of the grains, so that the scandium and magnesium elements are distributed more evenly, the brittle failure and microcracks of the material are reduced, and the toughness and tensile strength of the material are improved.

[0048] S6 secondary heat treatment: the cooled casting is put into a heating container for reheating;

[0049] Specifically, the rapidly cooled casting is put back into the heating furnace, heated to 120° C., and heated for 12 hours. The secondary heat treatment can diffuse the metal elements in the grains and ensure the uniform distribution of the metal elements.

[0050] S7 interface treatment: Use low voltage orthogonal overlapping current to treat the casting with a bipolar oxide film.

[0051] Specifically, the casting that has undergone secondary heat treatment is polished and ground, and the polishing agent can be silica, corundum, steel balls, etc. The polished casting is subjected to a low-voltage orthogonal overlapping current for a bipolar oxide coating treatment. The voltage of the orthogonal overlapping current is lower than 20V, of which direct current accounts for 60% and alternating current accounts for 40%. The thickness of the coating layer of the treated casting is above 100μm, which greatly improves the hardness and wear resistance of the alloy casting.

[0052] Example 2

[0053] The difference between this embodiment and embodiment 1 is that the scandium-containing aluminum alloy provided has different composition ratios, and is specifically composed of the following weight parts: 0.05% Sc, 2% Mg, 1.8% Cu, 8% Zn, 0.15% Zr, and the balance is Al.

[0054] Example 3

[0055] The difference between this embodiment and embodiment 1 is that the scandium-containing aluminum alloy provided has different composition proportions, and is specifically composed of the following weight parts: 0.02% Sc, 2% Mg, 1.8% Cu, 8% Zn, 0.2% Zr, and the balance is Al.

[0056] Example 4

[0057] The difference between this embodiment and embodiment 1 is that the content of aluminum alloy in the aluminum-zinc alloy ingot, aluminum-copper alloy ingot, aluminum-magnesium alloy ingot, aluminum-zirconium alloy ingot and aluminum-scandium alloy ingot in step S1 is 90%.

[0058] Comparative Example 1

[0059] The difference between this comparative example and Example 1 is that the scandium-containing aluminum alloy provided has a different composition ratio, specifically consisting of the following weight parts: 0.1% Sc, 2% Mg, 1.8% Cu, 8% Zn, 0.15% Zr, and the balance is Al.

[0060] Comparative Example 2

[0061] The difference between this comparative example and Example 1 is that the scandium-containing aluminum alloy provided has a different composition ratio, specifically consisting of the following weight parts: 0.02% Sc, 2% Mg, 1.8% Cu, 8% Zn, 0.05% Zr, and the balance is Al.

[0062] Comparative Example 3

[0063] The difference between this comparative example and Example 1 is that the content of aluminum alloy in the aluminum-zinc alloy ingot, aluminum-copper alloy ingot, aluminum-magnesium alloy ingot, aluminum-zirconium alloy ingot and aluminum-scandium alloy ingot in step S1 is 95%.

[0064] Comparative Example 4

[0065] The difference between this comparative example and Example 1 is that the content of aluminum alloy in the aluminum-zinc alloy ingot, aluminum-copper alloy ingot, aluminum-magnesium alloy ingot, aluminum-zirconium alloy ingot and aluminum-scandium alloy ingot in step S1 is 70%.

[0066] Comparative Example 5

[0067] The difference between this comparative example and Example 1 is that the cooling rate in step S5 is 10S.

[0068] Comparative Example 6

[0069] The difference between this comparative example and Example 1 is that direct current is used to perform bipolar oxide film treatment in step S7 interface treatment.

[0070] The performance test results of the scandium-containing aluminum alloys provided in the above embodiments and comparative examples are shown in Table 1 below:

[0071] Table 1: Example & Comparative Example Experimental Results

[0072]

[0073] Experimental results analysis:

[0074] The aluminum alloy containing scandium prepared in the present invention is prepared by doping aluminum with scandium, zinc, copper, magnesium and zirconium elements and limiting their contents, such as adding an appropriate amount of scandium element to refine the alloy grains. When the content of the scandium element is too high, as shown in the experimental data of comparative example 1, its grain refinement effect cannot be improved in the same proportion, but will aggravate the segregation phenomenon, resulting in a decrease in the mechanical properties of the alloy and a significant increase in the manufacturing cost. After the zirconium element is added, the tensile strength of the alloy can be improved.

[0075] The present invention aims at the phenomenon that component segregation is easy to occur in the production of the doping method. In the process of ingot production, the content of zinc, copper, magnesium, zirconium and scandium added to the master alloy is limited to 10% to 20%, so that the segregation phenomenon caused by too little content of the added alloy can be suppressed in the melt, and then the uneven distribution of the added alloy in the aluminum liquid can be reduced, thereby improving the alloy performance. From the experimental data of comparative examples 2 and 3, it can be seen that when the content of zinc, copper, magnesium, zirconium and scandium added to the master alloy is small, the strength of the alloy material will be significantly reduced, and excessive addition will also affect the mechanical properties of the alloy to a certain extent.

[0076] The inventors of the present invention creatively use a rapid cooling operation in the aluminum-scandium alloy to reduce the movement speed of the grains, so that magnesium and scandium elements will not only not segregate, but will be distributed more evenly, which can greatly reduce the low-temperature brittle failure and microcracks that occur when impurities segregate to the grains, and improve the toughness and tensile strength of the alloy material. If conventional cooling is used, as shown in the test data of comparative example 5, it can be seen that too slow cooling will cause the metals in the alloy elements, especially magnesium and scandium elements, to be unevenly distributed due to too fast movement, reducing the toughness and tensile strength of the alloy material.

[0077] In summary, the scandium-containing aluminum alloy prepared in the present invention is prepared by doping scandium and zinc, copper, magnesium and zirconium elements into aluminum, using a doping method and optimizing and innovating the original doping method, limiting the aluminum content in the primary alloy of aluminum and other metals, as well as rapid cooling and interface treatment, thereby reducing the occurrence of segregation in alloy production, refining the alloy grains, and improving the strength and ductility of the aluminum-scandium alloy.

[0078] At the same time, the present invention aims at the phenomenon that component segregation is easy to occur in the production of the doping method. In the ingot production process, the content of zinc, copper, magnesium, zirconium and scandium added to the intermediate alloy is limited to 10% to 20%. In this way, the segregation phenomenon caused by too little content of the added alloy can be suppressed in the melt, and then the uneven distribution of the added alloy in the aluminum liquid can be reduced, thereby improving the alloy performance.

[0079] Moreover, the inventors have found that in long-term research, scandium and magnesium are prone to rapid grain movement during cooling, resulting in obvious segregation. In view of the above phenomenon, the inventors creatively use a rapid cooling operation in the aluminum-scandium alloy, which can reduce the movement speed of the grains, so that magnesium and scandium elements will not only not segregate, but will be distributed more evenly, which can greatly reduce the low-temperature brittle failure and microcracks that occur when impurities segregate to the grains, and improve the toughness and tensile strength of the alloy material. Since the surface of the aluminum alloy is usually covered with a layer of oxide film, but the oxide film is very thin, it is impossible to effectively protect the aluminum alloy, so the thickness of the aluminum alloy oxide film is usually increased by electrochemical means. However, the native oxide film on the surface of the aluminum alloy will hinder the current during actual work. When the thickness of the oxide film becomes thicker and thicker, it is necessary to increase the voltage, resulting in a significant increase in power consumption and high heat generated due to long-term operation at high voltage, and then the film layer burns, and the film layer cannot be further thickened. In response to the above problems, the inventors used the overlapping method of AC + DC to oxidize the surface of the aluminum alloy. By controlling the generation speed and adjusting the size and number of pores on the surface of the aluminum alloy, the thickness of the oxide film can be increased to more than 100μm, which greatly improves the wear resistance, corrosion resistance and surface strength of the aluminum alloy.

[0080] It is obvious to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be regarded as exemplary and non-restrictive from any point of view. In addition, it should be understood that although this specification is described in accordance with the embodiments, it does not contain only one technical solution. This narrative of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole, and the technical solutions in the embodiments can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. A method for preparing a scandium-containing aluminum alloy, characterized in that: The following steps are involved: S1 Ingot production: metal aluminum is respectively put into a heating furnace with protective gas with zinc, copper, magnesium, zirconium and scandium for heating and melting, stirring and mixing, and then cooling to form aluminum-zinc alloy ingots, aluminum-copper alloy ingots, aluminum-magnesium alloy ingots, aluminum-zirconium alloy ingots and aluminum-scandium alloy ingots; the aluminum content of the aluminum-zinc alloy ingots, aluminum-copper alloy ingots, aluminum-magnesium alloy ingots, aluminum-zirconium alloy ingots and aluminum-scandium alloy ingots is 80% to 90%; S2: dissolving and casting: putting the ingot and metal aluminum obtained in S1 into a heating furnace with a protective gas to heat into a molten liquid, and then pouring the molten liquid into a casting mold and casting it under pressure to form a casting; in the steps S1 and S2, the heating furnace temperature is 730-750°C, the stirring time is ≥1h, the protective gas is nitrogen or argon, and the heating furnace pressure is 10-15mmHg; during pressure casting, the protective gas is sprayed, the protective gas temperature is 450-550°C, and the spraying pressure is 2-4bar; S3 surface treatment: wash the castings made in S2 and apply rust inhibitor; S4 heat treatment: the surface treated casting is put into a heating container for reheating, the heating temperature is 400-500°C, and the heating time is 100-150 minutes; S5 rapid cooling: rapidly cooling the heat-treated casting to room temperature, wherein the rapid cooling time is ≤ 2s; the cooling medium is liquid nitrogen or water; S6 secondary heat treatment: the cooled casting is put into a heating container for reheating at a temperature of 115-125°C for 12-24 hours; S7 interface treatment: Use low voltage DC / AC overlapping current to treat the casting with bipolar oxide film; The scandium-containing aluminum alloy consists of the following components by weight: 7-8% Zn, 1.6-2% Cu, 1.8-2.2% Mg, 0.1-0.2% Zr, 0.02% Sc, and the balance is Al.

2. The method for preparing a scandium-containing aluminum alloy according to claim 1, characterized in that: In step S3, the washing solution is a 10% nitric acid solution, and the rust inhibitor is a tribasic hydroxy acid.

3. The method for preparing a scandium-containing aluminum alloy according to claim 1, characterized in that: In step S7, the voltage of the bipolar oxide film treatment is ≤20V, the DC / AC overlapping current is 40% AC and 60% DC; and the oxide film thickness is ≥100µm.

Citation Information

Patent Citations

  • Aluminum alloy anode oxidation technology

    CN107641827A

  • Aluminum alloy material

    JP2022119334A